Efficacy of Antiviral Medications in Decreasing Inflammation Levels Among Covid-19 Patients Experiencing Chronic Kidney Disease (CKD) - Fendy Prasetyawan; Faisal Akhmal Muslikh; Anis Akhwan Dhafin; Elsa Mahardika Putri; Yuneka Saristiana; Susilo Margining Raharjo (Contemporary Journal of Applied Sciences, 2023)
Individuals with Chronic Kidney Disease (CKD) face an elevated risk of severe COVID-19 infection. A comprehensive investigation into the effectiveness of antiviral medications in treating COVID-19 patients is imperative. The primary goal is to assess the severity of the illness and the efficacy of antiviral drugs in individuals with COVID-19 and CKD following antiviral treatment at Dr. Soedomo Trenggalek Hospital. This study adopts a cross-sectional approach, employing purposive sampling for sample selection. Retrospective data from 2022 medical records of COVID-19 patients diagnosed with CKD are analyzed. The research findings highlight the efficacy of antiviral drugs in diminishing inflammation levels in COVID-19 patients, as indicated by a significant p-value of 0.000. However, the leukocyte data proved inadequate in determining the reduction in inflammatory levels. Therefore, obtaining data on C-reactive protein (CVR) and lymphocytes is crucial for a more accurate measurement. The p-value for ClCr is 0.842.